Transformasi Digital Pelayanan Rumah Sakit Melalui Sistem Informasi Rawat Inap dan Rawat Jalan Berbasis Web di Rumah Sakit Umum Daerah (RSUD) Kota Prabumulih - Aditya Fersta Alwi; Evi Yulianingsih (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2026)
Digital transformation has become an essential necessity in improving the quality of healthcare service, including the management of patient and outpatient services.Rumah Sakit Umum Daerah (RSUD) Kota Prabumulih faces various challenges in managing patient data, administrative record-keeping, and presenting information that is not yet optimally integrated. These conditions affect the efficiency of staff performance and the overall quality of service provided to patients. This study aims to design and implement a web-based inpatient and outpatient information system as part of the hospital’s digital transformation efforts. The system is developed using web-based technology integrated with a database to manage patient data, registration processes, and reporting. The results of study indicate that the developed information system is able to improve the speed, accuracy, and percision of data management, as well as facilitate easier acces to information of the hospital. Therefore, the implementation of web-based inpatient and outpatient information system can support digital transformation and enhance the quality of healthcare services at RSUD Kota Prabumulih.